(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Erysipelas is an acute infectious disease caused by β-hemolytic Streptococcus group A, characterized by skin inflammation and febrile syndrome. Erysipelas remains a pressing issue in infectious dermatology and general medicine. The incidence of this pathology remains stable, especially among elderly individuals, in whom the course of the disease is often complicated by concomitant pathologies and reduced immune reactivity. An important task is timely diagnosis and prevention of complications such as lymphostasis, recurrences, abscesses, and phlegmon. Based on clinical and laboratory data, the severity of the disease, the frequency of complications, and their risk factors were assessed.